Draft genome sequences of two textile azo dye-degrading Shewanella sp. Strains isolated from a textile effluent in Peru - Fuentes I. (2019)
Here, we report the annotated genome sequences of two Shewanella sp. strains isolated from textile industry wastewater effluent in Peru. Potential genes for encoding enzymes that enable the strain to decolorize and degrade textile azo dyes were detected in both genomes. © 2019 Fuentes et al.